THE ROLE OF SOYBEAN IN CONTROL OF DEGENERATIVE DISEASE - Nanda Triandita; Nela Eska Putri (Jurnal Teknologi Pengolahan Pertanian, 2019)
ABSTRACTDegenerative disease is a chronic non-communicable disease that occurs due to a decline in the function of cells or organs of the body as we get older. Degenerative diseases can occur preceded by a decrease in environmental and social conditions, changes in the body's metabolism by decreasing hormone production at the age of 65 years and over, shifting diet and lifestyle to a modern diet with high fat but low in fiber and carbohydrates, impact on increasing body cholesterol and excess nutrients that support increased oxidative stress. Soybean is the main source of vegetable protein and vegetable oil in the world. The main use of soy is from seeds. Soybean seeds are rich in protein and fat as well as several other important nutrients, such as vitamins (phytic acid) and lecithin. Research on the benefits of soy and its processed products in controlling degenerative diseases such as hypertension, hypercholesterolemia, diabetes mellitus, cancer and others has been carried out. This benefit is obtained from the composition of soybeans rich in nutritional components such as protein and essential amino acids, vegetable fats, vitamins and minerals, as well as non-nutritional components such as food fiber and bioactive components. Soybean acts as an ACE-inhibitor and lowers blood cholesterol and has the potential to inhibit hypertension and coronary heart disease. In controlling diabetes, soy can reduce blood glucose levels, insulin resistance and inflammation, and maintain blood lipid profile. Soybeans play a role in inhibiting the proliferation of cancer cells and reducing inflammation so as to reduce the risk of colon cancer. Soy isoflavones act as an estrogen hormone that can increase the absorption of calcium in preventing osteoporosis. The potential benefits of soy and its preparations in reducing the risk of degenerative diseases can be used as healthy food on a daily diet.Keyword: Coronary heart disease, Degenerative diseases, Diabetes, Hypertension, Soybean